PARTAI DEMOKRASI INDONESIA (PDI) IN GORONTALO THE NEW ORDER ERA - Mayang Rasti, Wa Ode; Apriyanto, Joni; Manay, Helman (CV. Fahr Publishing, 2024)
The aim of this research is to understand the dynamics of the Indonesian Democratic Party (PDI) in general elections in Gorontalo. The method used is the historical research method, which follows four procedural steps: First, Heuristics, which involves the collection or investigation of historical sources. Second, Verification or Source Criticism, which tests the authenticity and accuracy of sources. Third, Interpretation or Analysis of the findings. Fourth, Historiography, which involves formulating the research results into a scholarly work with high-quality historical writing. The research findings reveal that the Indonesian Democratic Party (PDI) was established in Gorontalo in 1977 as a result of a party merger. During the New Order era, PDI faced significant limitations, as the government at the time leaned more towards Golkar. As a result, in five consecutive general elections during the New Order in Gorontalo, PDI never emerged as the winning party and consistently ranked third. Despite repeated losses in elections, the party, which carried the Marhaenist ideology, remained resilient. Various efforts were made to strengthen its support base, including direct engagement with the community. This culminated in 1997, following the Kudatuli incident, which led to the formation of the Indonesian Democratic Party of Struggle (PDI-P). This event brought significant changes to PDI’s party structure, and in the subsequent elections, PDI emerged as the winning party.